2010
DOI: 10.1103/physrevc.81.045203
|View full text |Cite
|
Sign up to set email alerts
|

Role of five-quark components in radiative and strong decays of theΛ(1405)resonance

Abstract: Within an extended chiral constituent quark model, three-and five-quark structure of the S 01

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 82 publications
2
33
0
Order By: Relevance
“…The weaker contribution of Λ(1670)S 01 might be explained by the configuration mixing between Λ(1405)S 01 and Λ(1670)S 01 [42]. An et al also predicted the existence of configuration mixings within the Λ(1405)S 01 and Λ(1670)S 01 by analyzing the decay properties of Λ(1405)S 01 [19]. On the other hand, to well describe the data, it is needed a large amplitude of Λ(1520)D 03 in the reaction, which is about a factor of 2.5 larger than that derived in the SU(6)⊗O (3) plays a crucial role in the low energy region.…”
Section: A Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The weaker contribution of Λ(1670)S 01 might be explained by the configuration mixing between Λ(1405)S 01 and Λ(1670)S 01 [42]. An et al also predicted the existence of configuration mixings within the Λ(1405)S 01 and Λ(1670)S 01 by analyzing the decay properties of Λ(1405)S 01 [19]. On the other hand, to well describe the data, it is needed a large amplitude of Λ(1520)D 03 in the reaction, which is about a factor of 2.5 larger than that derived in the SU(6)⊗O (3) plays a crucial role in the low energy region.…”
Section: A Parametersmentioning
confidence: 99%
“…Theoretically, (i) the mass spectroscopes were predicted in various quark models [4][5][6][7][8][9][10][11][12][13], large N c QCD approach [12,13] and lattice QCD etc [14,15]; (ii) the strong decays were studied within different models [4,[16][17][18][19]; (iii) the properties of the individual resonances, such as Λ(1405), Λ(1670) and Λ(1520), were attempted to extract from the K − p scattering data with UχPT approaches [20][21][22][23][24][25][26][27][28][29][30][31][32][33], BχPT approaches [34], K-matrix methods [35,36], large-N c QCD method [37], meson-exchange models [38][39][40], quark model approaches [41,42], dispersion relations [43,44], and the other hadronic models [45][46][47]…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37], in order to reproduce the electromagnetic and strong decays of nucleon resonances, both R 35 > 1 and R 35 < 1 have been suggested. In [34][35][36][37] it was shown that the most sensitive parameter is in fact the ratio 2ω 3 ω 5 /(ω 2 3 + ω 2 5 ). It is thus very difficult to judge whether R 35 is less than 1 or not.…”
Section: B Dependence Of Numerical Results On Parametersmentioning
confidence: 99%
“…Within that approach, the electromagnetic and strong decays properties of the P 31 (1232) [5], P 11 (1440) [6], S 11 (1535) [7] and S 01 (1405) [8,9] resonances are well described.…”
Section: Introductionmentioning
confidence: 97%
“…Here we will follow the formalism for strong decays in Ref. [8], where the coupling of a resonance to meson-baryon channel is obtained by calculating the matrix element of the following operators:…”
Section: Theoretical Frameworkmentioning
confidence: 99%